Prevalence of bacterial contaminants in domestic kitchen sinks and laundry machines in houses of Mosul, and the effect of common disinfectants - Ghada A. M. Al-Taee; Sahar S. B. Al-Naqqar; Shababa A. Bahjet (College of Education for Pure Sciences, 2007)
ABSTRACT A total of (107) samples, (54) from kitchen sinks, and (53) from laundry machines were obtained from houses in the city of Mosul . Samples were analyzed for the Presence of Mesophilic aerobic bacteria, Pseudomonas, Staphylococci, and enterobacteriaceae. Results showed that 94.4 % of sink samples were contaminated with one or more microorganisms. Pseudomonas and Klebsiella were the two dominant bacteria in addition to coagulase negative micrococcaceae, E. coli, Citrobacter, Enterobacter, Proteus and Salmonella. Also, 69% of laundry machines were contaminated mostly with pseudomonas, and coagulase negative micrococcaceae , in addition to Enterobacter and Citrobacter . disinfectant were evaluated against Pseudomonas aeroginosa and Klebsiella :Lenol, Fenetol, Hexavlon, Aredol, Chloroxylenol, and Na-hypochlorite. The latter was the most effective shortly after its addition .